2020
DOI: 10.1111/hae.14232
|View full text |Cite
|
Sign up to set email alerts
|

Women and girls with haemophilia and bleeding tendencies: Outcomes related to menstruation, pregnancy, surgery and other bleeding episodes from a retrospective chart review

Abstract: Introduction Women or girls with haemophilia (WGH) represent a group of female symptomatic carriers who experience bleeding events more frequently than non‐carriers. Bleeding events include spontaneous/traumatic bleeds and prolonged bleeding related to surgery, menstruation and pregnancy. Challenges for the treatment of WGH include lack of screening, diagnosis and treatment guidelines. Aim Evaluate clinical characteristics, haemostasis management and clinical outcomes regarding menstruation, childbirth, dental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…A retrospective study by Chaudhury et al found that antifibrinolytics were the most utilized treatment (used in 50%) for HMB in WGH, followed by desmopressin and factor concentrates (used in 29% and 14%, respectively). 54 Non-steroidal anti-inflammatory drugs (NSAIDs) are used for HMB in the general population but are not recommended in patients with IBD given their antiplatelet effects. Desmopressin can be used in patients with VWD or Haemophilia A who have been shown to be responsive.…”
Section: Iron Deficiency and Iron Deficiency Anaemiamentioning
confidence: 99%
See 2 more Smart Citations
“…A retrospective study by Chaudhury et al found that antifibrinolytics were the most utilized treatment (used in 50%) for HMB in WGH, followed by desmopressin and factor concentrates (used in 29% and 14%, respectively). 54 Non-steroidal anti-inflammatory drugs (NSAIDs) are used for HMB in the general population but are not recommended in patients with IBD given their antiplatelet effects. Desmopressin can be used in patients with VWD or Haemophilia A who have been shown to be responsive.…”
Section: Iron Deficiency and Iron Deficiency Anaemiamentioning
confidence: 99%
“…Tranexamic acid is particularly helpful in those wishing to conceive and those with heavy bleeding with normal duration. A retrospective study by Chaudhury et al found that antifibrinolytics were the most utilized treatment (used in 50%) for HMB in WGH, followed by desmopressin and factor concentrates (used in 29% and 14%, respectively) 54 . Non‐steroidal anti‐inflammatory drugs (NSAIDs) are used for HMB in the general population but are not recommended in patients with IBD given their antiplatelet effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 , 38 Across the lifespan, women with bleeding disorders require specialized care that includes attention to heavy menstrual bleeding pre-menopause, 39 as well as pre- and post-surgery planning to control for heavy blood loss associated with surgery, pregnancy, and postpartum and during times of spontaneous and traumatic joint bleeding. 40–42 …”
Section: Unique Benefits Of Integrated Care Provided By Htcsmentioning
confidence: 99%
“… 12 Menorrhagia is often present but is not invariable. 40 , 41 On a standardized bleeding assessment tool, the International Society on Thrombosis and Haemostasis Bleeding Assessment Tool, women heterozygous for HA or HB scored higher than controls in the categories of cutaneous, minor wound, oral cavity, menorrhagia, hemarthrosis, post dental, postsurgical, and postpartum bleeding, and there was a significant inverse correlation between factor level and bleeding score. 42
Figure 2 Distributions of factor IX activity in women heterozygous for variants causing hemophilia B (heterozygotes) and for women not having variants causing hemophilia (controls).
…”
Section: Heterozygous Females (Carriers)mentioning
confidence: 99%